Study of Ventilator-Associated Pneumonia in a Pediatric Intensive Care Unit - Balasubramanian, Pooja; Tullu, Milind S. (Indian journal of pediatrics, 2014)
Objectives To determine the incidence, etiology, risk factors and outcome of ventilator associated pneumonia (VAP) among mechanically ventilated patients. Methods All PICU patients who were mechanically ventilated for >48 h were consecutively enrolled. The development of VAP was defined by the radiological and clinical criteria described by the Center for Disease Control and Prevention/National Nosocomial Infection Surveillance (CDC/NNIS) (2003). The risk factors for VAP were determined by univariate and multivariate analysis using appropriate statistical methods. Results The median age of the subjects ( N = 232) was nine mo with a male to female ratio of 1.3:1. Of 232 subjects enrolled, there were 15 episodes of VAP in 14 patients (frequency of 6.03 %) with a mean VAP rate of 6.3/1,000 ventilator days. Eight of the 15 VAP episodes showed positive endotracheal culture with Gram negative organisms as the predominant isolate with Acinetobacter being the commonest organism isolated (62.5 %). Neuromuscular disease ( P = 0.005), histamine-2 receptor blockers ( P = 0.0001), tracheostomy ( P = 0.0001), and positive blood culture growth ( P = 0.0008) were found to be significantly associated with VAP (univariate analysis). VAP patients had a significantly longer duration of mechanical ventilation (22.5 vs. 5 median days; P < 0.001), longer PICU stay (23.25 vs. 6.5 median days; P < 0.001) and longer hospital stay (43.75 vs. 13.25 median days; P < 0.001). On multivariate analysis, only positive blood culture growth was a risk factor for VAP. The mortality rate of VAP was 42.8 % (not higher than those without VAP). Conclusions Frequency of VAP was 6.03 % with neuromuscular disease, histamine-2 receptor blockers, tracheostomy and positive blood culture being risk factors for VAP.